First Isolates of OXA-48-Like Carbapenemase-Producing Enterobacteriaceae in A Specialized Cancer Center - Villanueva-Cotrina, F (2022)
Background: OXA-48-like carbapenemases have been found in a growing and varied number of carbapenemase-producing Enterobacteriaceae (CPE) isolates, and they are spreading to several countries. Although this oxacillinase leads to weak resistance to carbapenems without affecting broad-spectrum cephalosporin activity, when they are associated with other resistance mechanisms, the level of resistance to these antibiotics may be significantly higher. This weak resistance against carbapenems and cephalosporins, along with the absence of other resistance mechanisms, could render OXA-48-like harboring isolates undetected in the laboratory routine. In addition, the lack of a specific screening test for this enzyme complicates the detection of these isolates. This report characterizes the first isolates of OXA-48-like CPE detected in our laboratory. Materials and Methods: The study was carried out at the Instituto Nacional de Enfermedades Neoplasicas, Lima - Peru, between March and December 2021. OXA-48-like CPE isolates were detected as part of the routine microbiological study, and clinical data were obtained by reviewing medical records. The automated microbiological system provides the bacterial identification and antimicrobial susceptibility profile by the dilution method. Additionally, the column chromatography test is used to detect carbapenemase enzymes, including OXA-48-like. Finally, the molecular identification of the OXA-48-like enzyme was carried out by Polymerase Chain Reaction PCR amplification for the blaOXA-48-like. Results: Seven OXA-48-like CPE strains were isolated. Notably, in all cases, the automated system issued a minimum inhibitory concentration (MIC) of ≥1 ug/mL for ertapenem and a MIC of >64/4 ug/mL for piperacillin/tazobactam. In addition, resistance category to imipenem and meropenem was found (2/7), at least one indeterminate category for any of these carbapenems (5/7), and other serine β-lactamases such as Extended-spectrum beta-lactamases (3/7) and AmpC (3/7). The immunochromatographic study confirmed the presence of the OXA-48-like enzyme in all isolates, while class A and class B were ruled out for them. Finally, the multiplex PCR, for the five isolates that could be recovered, showed amplification for carbapenemase OXA-48-like, while none of the other carpabemases was amplified for class A or class B carbapenemase genes. Conclusion: We confirm the emergence of OXA-48-like CPE isolates in our cancer center and highlight the need to implement surveillance and detection measures of these strains, for controlling their dissemination. We found practical and inexpensive methodologies for the detection of OXA-48-like CPE: (1) the finding of resistance to ertapenem and piperacillin/ tazobactam in the antibiogram in the absence of class A and B carbapenemases, for screening and (2) immunochromatographic study, for confirmation.